Abnormal visual gain control and excitotoxicity in early-onset Parkinson's disease Drosophila models. - Himmelberg, M.M.; West, R.J.H.; Elliott, C.J.H.; Wade, A.R. (Journal of Neurophysiology, 2018)
The excitotoxic theory of Parkinson's disease (PD) hypothesizes that a pathophysiological degeneration of dopaminergic neurons stems from neural hyperactivity at early stages of disease, leading to mitochondrial stress and cell death. Recent research has harnessed the visual system of Drosophila PD models to probe this hypothesis. Here, we investigate whether abnormal visual sensitivity and excitotoxicity occur in early-onset PD (EOPD) Drosophila models DJ-1??72, DJ-1??93, and PINK15. We used an electroretinogram to record steady-state visually evoked potentials driven by temporal contrast stimuli. At 1 day of age, all EOPD mutants had a twofold increase in response amplitudes compared with w? controls. Furthermore, we found that excitotoxicity occurs in older EOPD models after increased neural activity is triggered by visual stimulation. In an additional analysis, we used a linear discriminant analysis to test whether there were subtle variations in neural gain control that could be used to classify Drosophila into their correct age and genotype. The discriminant analysis was highly accurate, classifying Drosophila into their correct genotypic class at all age groups at 50-70% accuracy (20% chance baseline). Differences in cellular processes link to subtle alterations in neural network operation in young flies, all of which lead to the same pathogenic outcome. Our data are the first to quantify abnormal gain control and excitotoxicity in EOPD Drosophila mutants. We conclude that EOPD mutations may be linked to more sensitive neuronal signaling in prodromal animals that may cause the expression of PD symptomologies later in life. NEW & NOTEWORTHY Steady-state visually evoked potential response amplitudes to multivariate temporal contrast stimuli were recorded in early-onset PD Drosophila models. Our data indicate that abnormal gain control and a subsequent visual loss occur in these PD mutants, supporting a broader excitotoxicity hypothesis in genetic PD. Furthermore, linear discriminant analysis could accurately classify Drosophila into their correct genotype at different ages throughout their lifespan. Our results suggest increased neural signaling in prodromal PD patients.